2014
DOI: 10.1186/1471-2105-15-s6-s6
|View full text |Cite
|
Sign up to set email alerts
|

Functional and genetic analysis of the colon cancer network

Abstract: Cancer is a complex disease that has proven to be difficult to understand on the single-gene level. For this reason a functional elucidation needs to take interactions among genes on a systems-level into account. In this study, we infer a colon cancer network from a large-scale gene expression data set by using the method BC3Net. We provide a structural and a functional analysis of this network and also connect its molecular interaction structure with the chromosomal locations of the genes enabling the definit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…The possibility that acquired behavior or marks can be passed from parents to children is in serious debate and the advent of epigenetics is hailed as a profound shift in our understanding of inheritance, i.e. that genes also have a kind of "memory" [23], [24], epigenetics being an upcoming hype in medical research [25], with a very recent example in cancer research found here [26].…”
Section: Lamarck's Theorymentioning
confidence: 97%
“…The possibility that acquired behavior or marks can be passed from parents to children is in serious debate and the advent of epigenetics is hailed as a profound shift in our understanding of inheritance, i.e. that genes also have a kind of "memory" [23], [24], epigenetics being an upcoming hype in medical research [25], with a very recent example in cancer research found here [26].…”
Section: Lamarck's Theorymentioning
confidence: 97%
“…The basic idea of BC3Net is a bagging version of C3Net [28] which gives conservative estimates of the relations between the variables using estimates of mutual information values. Previously, this method has been successfully used in genomics to infer causal gene regulatory networks from high-dimensional data [29,30] and in finance for inferring investor trading networks [31].…”
Section: Global Community Landscapementioning
confidence: 99%
“…Clustering techniques have been applied to medical problems for some time and there are many different algorithms available, all with very different performances and use cases [26], [27], [28], [29].…”
Section: Cluster Analysis By Dbscan Algorithmmentioning
confidence: 99%